Mrs. Jekyll Meets Mrs. Hyde: The War Advertising Council, Rhetorical Norms, and the Gendered Home Front in World War II. Issue 1 (1st January 2018) - Kimble, James J.
Abstract : This article presents a study of the rhetorical dynamics of patriarchal advertising in the United States during World War II. The analysis scrutinizes a series of War Advertising Council (WAC) ads that targeted a wide swath of women on the home front, doing so through the depiction of negative and positive role models. The essay concludes that in these sorts of appeals WAC tacitly relied on rhetorical norms, which acted as a gendered means of patriarchal control in the face of the increased wartime autonomy that was enjoyed by many women during the war years.